Brief recommendations for participation in leisure time or competitive sports in athletes–patients with coronary artery disease: Summary of a Position Statement from the Sports Cardiology Section of the European Association of Preventive Cardiology (EAPC). (29th August 2020) - Borjesson, Mats; Dellborg, Mikael; Niebauer, Josef; LaGerche, Andre; Schmied, Christian; Solberg, Erik E; Halle, Martin; Adami, Paolo Emilio; Biffi, Alessandro; Carré, Francois; Caselli, Stefano; Papadakis, Michael; et al.
Abstract: This paper presents a brief summary of the recommendations from the Sports Cardiology section of the European Association of Preventive Cardiology (EAPC) on sports-participation in patients with coronary artery disease, coronary artery anomalies or spontaneous dissection of the coronary arteries, all entities being associated with myocardial ischaemia. 1 Given the wealth of evidence supporting the benefits of exercise for primary and secondary prevention of coronary artery disease, individuals should be restricted from competitive sport only when a substantial risk of adverse event or disease progression is present. These recommendations aim to encourage regular physical activity including participation in sports and, with reasonable precaution, ensure a high level of safety for all individuals with coronary artery disease. The present document is based on available current evidence, but in most instances because of lack of evidence, also on clinical experience and expert opinion.